PENERAPAN STRATEGI MODELLING THE WAY PASSING ATAS PADA PERMAINAN BOLA VOLI - Madwerdi, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The objective of the research is to improve the learning achievement of passing up on the game of volleyball through the application of modeling strategy the way to improve the quality of student learning outcomes in following the learning process which is shown by the result of the performance test, the students attitude and the better student behavior. Class action. The results of research conducted, there is an increase in student learning outcomes from the initial conditions to the cycle 1 and cycle II, both from penigkatan average value of learning passing up and the value of learning result completeness. The initial average initial value (55.875), the average cycle I (67.416) and the average cycle II (76.125), so that the increase from initial condition to cycle II (20.25). The increase of movement ability in passing up learning can be seen from the value of KKM (65) after the action is done on the cycle 1 student learning value complete as much as 19 out of 24 students (79,16%) and in cycle II which have value above KKM counted 22 from 24 Total or complete students (91.66%). Keyword : Top Passing Volleyball, The Modeling Strategy The Way.